L’hétérodoxie indigène au cœur des conflits intrasociaux dans le Pérou colonial : perception et analyse de Bartolomé Álvarez, doctrinero de la fin du XVIème siècle. - Nejma Kermele (Centre de Recherches sur les Mondes Américains, 2009)
This article proposes a short analysis of a document written by a priest named Bartolomé Álvarez in Bolivia of the end of the XVIth century. This Memorial a Felipe II is immediately posterior to the IIIrd Council of Lima and the reforms of Don Francisco de Toledo. Bartolomé Álvarez summarizes in this work the conflict between a religious standard and many indigenous idolatries. The text exposes, sometimes with a real violence, the elements of the conflict between Spaniards and Indians. These conflicts seem irreducible and dangerous for the Iberian power. Then the religious heterodoxy becomes political dissidence and makes possible the unabashed recourse to force. Bartolomé Álvarez affirms in this text that only the construction of a truly colonial society will allow the imposition of the evangelization and an enduring Spanish presence in America.